Considering Students’ Prior Knowledge in Culture-based Contextual Learning Media Application: How Effective It is to Support Students’ Mathematics Learning Outcome - Zainnur Wijayanto; Rahayu Retnaningsih (Universitas Tidar, 2019)
The present study aims to describe the effectiveness of culture-based contextual mathematics learning media by considering students’ prior knowledge. This is a quasi-experimental study that employed pretest-postest non-equivalent group design. Eight graders of a Junior High School (JHS) in Yogyakarta were involved as experimental and control groups. The data were obtained through a test to find out the students' mathematics learning achievements, while the data analysis technique used is the analysis of two-way variance with unequal cells. The results indicate that by considering the students’ previous knowledge, the culture-based contextual mathematics learning media is more effective than the conventional ones.